(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The software community intends to make use of a standard approach for the software development to not build software product from scratch. This approach ensures a high quality of software with a controllable cost. It affects the whole process of the softwareÂ development, especially in theÂ early phases e.g. analysis and design. One of the most widespread language to modulate and document those two stages is UML (Unified Modeling Language), but the reuse of the UML model is used in ad-hoc method so why do not build a systematic method for reusing some fragments of UML? To realize it, we need to adopt a reuse approach, so we choose the software product line (SPL), based in collecting variability of the domain (in our case is UML). In fact, UML and SPL have a common issue is the model driven engineering, since both of them based on the modeling approach. This paper overviews the different areas of UML and explains the process of software Product line with its born issues to wit: MDE (Model Driven Engineering) and MDA (Model Driven Architect).